Analysis of retrieved STRYDE nails. (1st August 2021) - Hothi, Harry; Bergiers, Sean; Henckel, Johann; Iliadis, Alexis D.; Goodier, William David; Wright, Jonathan; Skinner, John; Calder, Peter; Hart, Alister J.
Abstract : Aims: The aim of this study was to present the first retrieval analysis findings of PRECICE STRYDE intermedullary nails removed from patients, providing useful information in the post-market surveillance of these recently introduced devices. Methods: We collected ten nails removed from six patients, together with patient clinical data and plain radiograph imaging. We performed macro- and microscopic analysis of all surfaces and graded the presence of corrosion using validated semiquantitative scoring methods. We determined the elemental composition of surface debris using energy dispersive x-ray spectroscopy (EDS) and used metrology analysis to characterize the surface adjacent to the extendable junctions. Results: All nails were removed at the end of treatment, having achieved their intended lengthening (20 mm to 65 mm) and after regenerate consolidation. All nails had evidence of corrosion localized to the screw holes and the extendable junctions; corrosion was graded as moderate at the junction of one nail and severe at the junctions of five nails. EDS analysis showed surface deposits to be chromium rich. Plain radiographs showed cortical thickening and osteolysis around the junction of six nails, corresponding to the same nails with moderate – severe junction corrosion. Conclusion: We found, in fully united bones, evidence of cortical thickening and osteolysis that appeared to be associated with corrosion at the extendable junction; when corrosion was present, cortical thickening was adjacent to this junction. Further work, with greater numbers of retrievals, is required to fully understand this association between corrosion and bony changes, and the influencing surgeon, implant, and patient factors involved. Cite this article: Bone Jt Open 2021;2(8):599–610.